Comparative anatomy of the mammalian neuromuscular junction - Boehm, Ines; Alhindi, Abrar [UNESP]; Leite, Ana S. [UNESP]; Logie, Chandra; Gibbs, Alyssa; Murray, Olivia; Farrukh, Rizwan; Pirie, Robert; Proudfoot, Christopher; Clutton, Richard; Wishart, Thomas M.; Jones, Ross A.; et al. (Wiley, 2020)
The neuromuscular junction (NMJ)—a synapse formed between lower motor neuron and skeletal muscle fibre—represents a major focus of both basic neuroscience research and clinical neuroscience research. Although the NMJ is known to play an important role in many neurodegenerative conditions affecting humans, the vast majority of anatomical and physiological data concerning the NMJ come from lower mammalian (e.g. rodent) animal models. However, recent findings have demonstrated major differences between the cellular anatomy and molecular anatomy of human and rodent NMJs. Therefore, we undertook a comparative morphometric analysis of the NMJ across several larger mammalian species in order to generate baseline inter-species anatomical reference data for the NMJ and to identify animal models that better represent the morphology of the human NMJ in vivo. Using a standardized morphometric platform (‘NMJ-morph’), we analysed 5,385 individual NMJs from lower/pelvic limb muscles (EDL, soleus and peronei) of 6 mammalian species (mouse, cat, dog, sheep, pig and human). There was marked heterogeneity of NMJ morphology both within and between species, with no overall relationship found between NMJ morphology and muscle fibre diameter or body size. Mice had the largest NMJs on the smallest muscle fibres; cats had the smallest NMJs on the largest muscle fibres. Of all the species examined, the sheep NMJ had the most closely matched morphology to that found in humans. Taken together, we present a series of comprehensive baseline morphometric data for the mammalian NMJ and suggest that ovine models are likely to best represent the human NMJ in health and disease.
Keywords: comparative anatomy; mammalian; neuromuscular junction; NMJ-morph; synapse